Performing music by a living composer: understanding the musical inspirations of Razak Abdul Aziz in selected piano works - Mohd Fairuz Zamani (2021)
Razak Abdul Aziz (1959 - ) has been inking down his music from the early 1980?s. Still writing newworks, he had composed music for various medium of instrumentations giving specialattention to the piano either as a soloist or a collaborator. Although this composer has beenin the contemporary music scene for nearly 40 years, scholarly writings on hiscompositions are extremely scarce. His works were only actively performed in the early1990s and only starting to regain attention in the recent years, locally and abroad. Thispractice-led research focuses on my take as a co-creator of the selected piano works of Razak AbdulAziz, viewing it using Rosenblatt?s three principles of Transactional Theory, while quotingexamples of inspirations in works by other composers to set the tone of the theoreticalframeworks of this dissertation. The research findings show that I, as the co-creator of thesechosen pieces, was able to document the journey of performing these works in an 80-minute recitalof solo and collaborative piano music of Razak Abdul Aziz, with prior discussions with thecomposer and intensive preparation with other musicians and production team. The findingalso demonstrates how the inspirations of the selected works are being translatedsufficiently into music notation, without being too technical with the music analysis.Music of Razak Abdul Aziz deserves more attention from both academics and performers, as thiscomposer is regarded as one of the earliest Malaysian contemporary music composers. It would be agreat loss to the nation should his works be continually neglected, causing them topossibly fall into oblivion.